2002
DOI: 10.1029/2001jd000445
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of denitrification on Arctic ozone depletion during winter 1999/2000

Abstract: [1] We have used the SLIMCAT three-dimensional chemical transport model together with observations from the Stratospheric Aerosol and Gas Experiment (SAGE III) Ozone Loss and Validation Experiment (SOLVE) and the Third European Stratospheric Experiment on Ozone (THESEO 2000) to quantify the effect of denitrification on Arctic ozone loss. We have used two different denitrification schemes in the model: one based on the sedimentation of ice particles containing cocondensed nitric acid trihydrate (NAT) and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 61 publications
(83 reference statements)
1
71
0
Order By: Relevance
“…The composition of liquid aerosols is calculated analytically (Luo et al, 1995). The ice particles are assumed to incorporate HNO 3 in the form of NAT described by a bimodal size distribution (Davies et al, 2002). Cl y and Br y are explicitly calculated from their long-lived sources at the surface and are therefore time dependent.…”
Section: The Simulations With Mimosa-chim Ctmmentioning
confidence: 99%
“…The composition of liquid aerosols is calculated analytically (Luo et al, 1995). The ice particles are assumed to incorporate HNO 3 in the form of NAT described by a bimodal size distribution (Davies et al, 2002). Cl y and Br y are explicitly calculated from their long-lived sources at the surface and are therefore time dependent.…”
Section: The Simulations With Mimosa-chim Ctmmentioning
confidence: 99%
“…The vertical transport is derived from ECMWF vertical winds. SLIMCAT simulations are performed with a recent version in which ozone fields are extended down to the troposphere on hybrid σ −θ coordinate (Feng et al, 2005). The model is forced by ECMWF analyses (instead of UKMOUnited Kingdom Met.…”
Section: Measurements and Modelsmentioning
confidence: 99%
“…Ice is assumed to incorporate NAT as a co-condensate, removing nitric acid from the vapour phase. A simple NAT-based denitrification scheme is used (see Davies et al, 2001;Feng et al, 2005). SLIMCAT was initialized on 1 December 2002 from an ECMWF-forced multi-annual run which started in 1989.…”
Section: Slimcatmentioning
confidence: 99%
“…Previous studies have recognized the importance of understanding the sensitivity of polar processing and ozone loss quantification to different data sets: Davies et al (2002) showed that two SLIMCAT chemical transport model (CTM) runs driven by horizontal winds and temperatures from the ECMWF (European Centre for Medium-Range Weather Forecasts) and Met Office DAS led to significantly different patterns of denitrification and chlorine activation and consequently large differences in ozone loss of nearly 20 %. Similarly, Santee et al (2002) found significant discrepancies in PSC formation and composition between model runs that used Met Office temperatures with and without a 3 K reduction.…”
Section: Introductionmentioning
confidence: 99%